Suitability of Contact-Free Oxygen Optical Microsensors for Measuring Respiration and Photosynthesis in Green Algae - Zhang, Xin; Filser, Juliane (Frontiers in Environmental Science, 2017)
Oxygen optical microsensors are a sensitive method to monitor oxygen production and consumption in soils, sediments and aquatic systems. They have been used widely to analyze the activity and metabolism of aerobic organisms, also in ecotoxicological tests. We aimed to assess the suitability of a contact-free device to measure cell respiration and photosynthesis for future applications in ecotoxicological tests. One of the most important advantages of this modified method is that respiration and photosynthesis of test organisms which are contaminated with test chemicals can be measured without contact between sensor and test medium. Therefore, it avoids sensor contamination. In an array of calibration tests with Chlorella vulgaris in green algae medium, algae cell activity was well correlated with cell counts. Results clearly showed that, compared to O2 evolution rate, O2 assimilation rate measured by oxygen optical microsensors in a contact-free manner could better predict the algae cell counts. In a second test series we measured O2 assimilation rate in soil from a field experiment inoculated with different communities of terrestrial algae. No significant difference was observed when comparing measurements of their activity with microsensors to results obtained with the Warburg respiratory manometer. However, optical microsensors are much faster and more easily applied than the traditional manometer. Therefore, the developed method appears promising for application in ecotoxicological tests in the future.